Electrical Transport in Terbium-iron-transition Metal Mixed Oxides - SINGH, U.P.; THAKUR, A.N.; SINGH, S.V.; KUMAR, S.C. (Asian Journal of Chemistry, 2010)
This paper presents the results of electrical conductivity (σ) and seebeck coefficient (S) measurements on the pressed pellets of TbFeTO4 (where T = Fe, Cr, Mn and Co) in the temperature range 400-1200 K. It has been found that these compounds are essentially electronic semiconductor with σ values lying in the range 10-7 to 10-3Ω-1 m-1 around 408 K. The maximum value of σ has been observed for TbFeMnO4 and lowest for TbFe2O4. The log σT vs. T-1 as well as S vs. T-1 plots for the studied compounds have three linear regions separated by break temperatures T1 and T2 which are same in both the plots. The sign of S indicates that charge carriers are electrons in the studied temperature range. The electrical conduction in first range (T < T1) is extrinsic and occurs due to donor type centers. In the second (T1 < T < T2) and third (T > T2) ranges, electrical conduction is hopping type and occurs due to hopping of electrons from Fe2+ to Fe3+ in TbFe2O4, Co2+ to Fe3+ in TbFeCoO4 and Fe2+ to Cr3+ in TbFeCrO4. In TbFeMnO4, electrical conduction occurs due to hopping of electrons from Mn3+ to Mn4+ centers in the temperature range T1 < T < T2 and from Fe2+ to Mn3+ centers in the range T > T2.